Frontal Sinus Mucocele Mimicking Sphenoorbital Tumor: A Very Rare Case Report - Prihartomo, Gatot Aji; Sidharto, Bagus; Hakim, Muhammad ’Azmi (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2024)
Introduction: The paranasal sinus mucocele is a slow-growing mass that contains mucous. It can grow to vary in size, well-defined border, and fluctuating. Case description: A 51-year-old male with the chief complaint was a mass in his left eye 9 months before. The complaint began with a small swelling and it became bigger. He had no chronic flu-like syndrome previously. He admitted that he had no complaints with his vision or his hearing. The mass is as big as eight centimeters in diameter. The physical examination revealed that his left eye was protruded with left eye acuity was 6/6. He had paresis with an upward gaze in his left eye. At the palpation examination, it was soft, elastic, and fluctuative, well-defined border with bony in its surroundings, and no pain sensation. Discussion: In this case, the frontal sinus mucocele can make the eyeball protrude because of downward development. It does not impair visual function, because it does not disturb the optic nerve. The impairment was difficult to gaze upwardly. Conclusion: Given that the lesion came from the frontal sinus, it could grow outwardly and make the eyeball protrude. Histologically, mucocele had to spread inflammatory cells and macrophages, debris cells, and necrotic mass. Keywords: Frontal sinus; mucocele; sphenoorbital tumor; paranasal sinus.